Efficient direct deoxygenation of bio-oil model compound (anisole) on highly dispersed SiO2-supported Ni3Ga intermetallic compound prepared by direct impregnation-reduction method. (October 2021) - Han, Yujun; Ai, Lin; Shi, Yinteng; Chen, Jixiang
Abstract: SiO2 supported Ni3 Ga intermetallic compound (IMC) with different nominal Ni contents ( x %Ni3 Ga/SiO2 ) were prepared by the simple impregnation-reduction method and evaluated for the hydrodeoxygenation of anisole (a representative bio-oil model compound) on a fix-bed reactor at 300 °C and 0.1 MPa. Different from the case that the calcination led to large NiO particle after the impregnation, nickel silicate rather than NiO were found without calcination. This results in highly dispersed Ni3 Ga IMC crystallites after the reduction. Nevertheless, the decrease of Ni3 Ga IMC crystallites size did not affect the electronic interaction between Ni and Ga and the surface Ni/Ga atomic ratio. Interestingly, the Ni3 Ga particles size ( 5.0 nm) did not become large with increasing the nominal Ni contents from 5% to 20%. Also, the spilt-over hydrogen species on x %Ni3 Ga/SiO2 were more easily desorbed than those on the catalyst via the calcinaiton. Consequently, x %Ni3 Ga/SiO2 gave higher reactivity in the direct deoxygenation of anisole to benzene. Given the turnover frequency (TOF) of anisole was affected by the Ni3 Ga crystallites size, we suggest that the HDO of anisole on Ni3 Ga/SiO2 was structure sensitive reaction. With increasing the nominal Ni content, there was an optimal performance on 15%Ni3 Ga/SiO2, where the conversion of anisole and the selectivity to benzene reached as high as 94.9% and 94.5%, respectively, remarkably higher than those (51.4% and 87.2%) on the Ni3 Ga/SiO2 prepared catalyst by the impregnation-calcination-reduction method. Highlights: Highly dispersed Ni3 Ga crystallites ( 5 nm) was prepared by impregnation-reduction. Increasing Ni3 Ga dispersion facilitated desorption of spilt-over hydrogen. Impregnation-reduction method result in good reactivity of Ni3 Ga/SiO2 . Anisole conversion and benzene selectivity reached 94.9% and 94.5%, respectively. HDO of anisole on Ni3 Ga/SiO2 was structurally sensitive.